Mô phỏng quá trình phục vụ người đọc ở một thư viện - Tân, Đoàn Phan (Journal of Computer Science and Cybernetics, 2016)
This article presents an application of queuing theory in order to establish a mathematical model for the process of service in a library or  in information center. On the basic of the model mentioned and applying the simulation method of  Monte-Carlo with properties of  random numbers, the author proposes an algorithm and a flowchart for writing a simulation program of this process. The input data if this program is composed: -Distribution of the number of andience’s requests. -Distribution of the service time. After running, this program will give the following information on  service system: Total of service time, total of writing time, total of free time, average of service time, average of writing time… Thus are sharacteristics features of the  service system.